2022
DOI: 10.1021/jacs.2c03883
|View full text |Cite
|
Sign up to set email alerts
|

Universal Kinetic Mechanism Describing CO2 Photoreductive Yield and Selectivity for Semiconducting Nanoparticle Photocatalysts

Abstract: Photocatalytic conversion of CO 2 to generate high-value and renewable chemical fuels and feedstock presents a sustainable and renewable alternative to fossil fuels and petrochemicals. Currently, there is a dearth of kinetic understanding to inform better catalyst design, especially at uniform reaction conditions across diverse catalytic species. In this work, we investigate 12 active, stable, and unique but common nanoparticle photocatalysts for CO 2 reduction at room temperature and low partial pressure in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…27). 132 To elucidate the role of the kinetics of elementary steps on Cu electrodes for CO 2 electroreduction, Janik and Asthagiri 71 presented a DFT study that considered the rate of electron-ion transfer reactions and provided an alternative reaction path that explained both the methane and ethylene production through a hydroxymethylidyne (COH) intermediate from CO reduction, which was consistent with experimental ndings. The study showed that considering solely the thermodynamics of reaction free energies was misleading for methane production, and the reaction kinetics of elementary steps were much more favorable for producing results consistent with the experimental data.…”
Section: Thermodynamics and Kinetics Of Intermediate Transformationsmentioning
confidence: 73%
“…27). 132 To elucidate the role of the kinetics of elementary steps on Cu electrodes for CO 2 electroreduction, Janik and Asthagiri 71 presented a DFT study that considered the rate of electron-ion transfer reactions and provided an alternative reaction path that explained both the methane and ethylene production through a hydroxymethylidyne (COH) intermediate from CO reduction, which was consistent with experimental ndings. The study showed that considering solely the thermodynamics of reaction free energies was misleading for methane production, and the reaction kinetics of elementary steps were much more favorable for producing results consistent with the experimental data.…”
Section: Thermodynamics and Kinetics Of Intermediate Transformationsmentioning
confidence: 73%
“…This characteristic supported that Ag-QDs were the active center of photoreduction. [25,48] Small 2023, 19, 2207234 According to the results of photooxidation and photoreduction experiments, it was believed that Ag-QDs should directly act as the reaction center in the SMSI metal/semiconductor system rather than just improved the semiconductor charge separation efficiency. Therefore, in situ P-TPD tests were designed to further confirm this hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…The photocatalytic solid-liquid reaction is usually carried out in the reactor equipped with a magnetic stirrer, and the motion of photocatalysts in suspensions results in a nonstable process of light absorption for each nanoparticle. [8][9][10] Incident photons are absorbed in variable positions within photocatalysts, which leads to the random generation of charge carriers. It is different from the generation of charge carriers in solar cells or photo-electro catalysis.…”
Section: The Solar Spectral Absorption Of Photocatalystsmentioning
confidence: 99%